Linkage analysis identifies novel loci in early‐onset Alzheimer disease in non‐Hispanic white families. (1st February 2022) - Jean‐Francois, Melissa N.; Pericak‐Vance, Margaret A.; da Fonseca, Eder Lucio; Baez, Penelope; Ayodele, Temitope; Welch, Jacob; Hamilton‐Nelson, Kara L.; Martin, Eden R.; Cuccaro, Michael L.; Reitz, Christiane; Beecham, Gary W.
Abstract: Background: Early‐onset Alzheimer disease (EOAD) is a highly genetic dementia typically defined as Alzheimer disease dementia with an age of onset of 65 years or younger. While known mutations in genes such as APP, PSEN1, and PSEN2 account for a small portion of EOAD, approximately 90% of all EOAD cases lack these known mutations. Since little is known about causes and course of EOAD, more research must be completed to identify the factors that contribute EOAD risk. To that end, we present here a genetic linkage analysis in multiplex EOAD families to identify loci likely to impact EOAD risk. Methods: Linkage analysis was performed on 21 non‐Hispanic white families (197 family members) with two or more individuals with EOAD (AAO ≤ 65 years). Genome‐wide array data were used to type single‐nucleotide polymorphisms. Merlin was used to perform parametric linkage analysis, non‐parametric linkage analysis, and two‐point parametric affected only analysis. Results: The two‐point parametric analysis identified 5 EOAD linkage regions with a HLOD score of 3.5 or greater (5q31.1[HLOD=5.18], 6p25.2 [HLOD=5.71], 9q31.1 [HLOD=3.65], 11q23.3 [HLOD=9.11], 15q24.3 [HLOD=5.86]). Regions 5q31.1, 6p25.2, 11q23.3, 15q24.3 generated HLOD scores greater than 4.0. Several Alzheimer disease (AD) associated genes were identified near these regions including PPT2, AGER, BACE1 . Using a suggestive linkage threshold of LOD ≥ 2.20, P = 7.4×10 −4, the parametric multi‐point analysis identified one linkage region at 4.p16.3 (LOD=2.35). The 1‐LOD unit interval for this region identified PDE5A, which has potential as a therapeutic target in several neurological diseases. Our non‐parametric linkage analysis identified 3 linkage regions with a LOD score equal to or exceeding the suggestive threshold of 2.20 (3p21.1 [LOD=2.21], 3p14.3 [LOD=2.28], 3p14.1[LOD=2.22]). The APPL1 gene, which has been linked to APP‐induced dysfunction, was located within the 1‐LOD unit interval of these regions. Conclusion: Several novel linkage EOAD regions have been identified that where not previously identified in known LOAD regions. The identification of these regions may provide information to establish EOAD as a separate disease from Late‐onset Alzheimer disease as well as provide therapeutic targets for AD.